Peran Rekam Medis Elektronik dalam Meningkatkan Kualitas Pelayanan Rawat Jalan di Klinik Pusdikarhanud - Nia Ariska; Lilik Afifah; Agus Syukron Ma'ruf (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
The development of information technology in the health sector has encouraged the implementation of Electronic Medical Records (EMR) as an effort to improve the quality of health services, particularly in outpatient care. EMR is expected to support smoother service flow and improve the quality of services at primary health care facilities. This study aims to analyze the role of Electronic Medical Records in improving the quality of outpatient services at Pusdikarhanud Clinic through five dimensions of service quality. This study used a descriptive qualitative method with data collected through in-depth interviews and observations. This research informants consisted of six individuals, including the head of the clinic, medical records officer, nurse, doctor, midwife, and pharmacist who were directly involved in outpatient services and the use of EMR. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The results of the study indicate that the implementation of EMR plays a positive role in improving the quality of outpatient services across five service quality dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles. EMR was found to accelerate service flow, improve patient data security, and support more patient-focused service interactions. However, challenges related to infrastructure and network stability as part of the tangible dimension, still need to be optimized to ensure more effective and sustainable EMR utilization.